Сomputer simulation of the stochastic dynamics in system of two coupled nonlinear oscillators - Syaber, S.S.; Anisimov, I.O. (Вопросы атомной науки и техники, 2013)
Dynamics of two coupled nonlinear oscillators has been studied. Oscillators are represented by conservative LC circuits with nonlinear capacitors. The system exhibits chaotic behavior in some range of initial conditions. Chaotic behavior is observed in one circuit if high amplitude oscillations are performed in the other circuit due to the appropriate initial conditions. Stochasticity of the oscillations is proved by the continuity of their spectrum and by the Poincare mapping.